The Public or Parties in the Media? A Study of Public, Party and Media Issue Agendas in Five Danish Election Campaigns - Hopmann, David Nicolas; Præstekær, Elmelund; Albæk, Erik; de Vreese, Claes H. (Javnost-The Public, 2009)
As the media plays a central role in the way modern democracies function, it is important to study whether the media engages in a top-down or a bottom-up mode of covering election news. The article studies whether the media agenda is congruent with the parties’ and the public’s agenda by analysing the three gendas in five national Danish election campaigns. Theoretically, increased professionalisation of politicians’ efforts to influence media coverage suggests convergence between the media and the party agendas, while increased commercialisation of the media suggests convergence between the media and the public agendas. However, since both the professionalisation of the parties and the commercialisation of the media are ongoing processes, convergence between all three agendas may be expected. Results show that the media agenda is slightly more similar to the agenda of the parties, but in general the media seems to be rather good at balancing their obligations to represent the issues of the elite on the one hand and to give voice to public concerns on the other. During the past two decades no convergence between the agendas is found, i.e. the interaction of the three different agendas is rather stable.